Insights Into the Significance of the Chinense Loess Plateau for Preserving Biodiversity From the Phylogeography of Speranskia tuberculata (Euphorbiaceae) - Ye, Jun-Wei; Wu, Hai-Yang; Fu, Meng-Jiao; Zhang, Pei; Tian, Bin (Frontiers in Plant Science, 2021)
The significance of the Chinese Loess Plateau (CLP) in maintaining biodiversity in North China has barely been uncovered, as previous phylogeography of wood species has revealed that the Quaternary refugia are mainly located in mountain regions. We selected a drought-enduring endemic herb, Speranskia tuberculata, to determine its glacial refugia and postglacial demographic history. Four chloroplast fragments, two low-copy nuclear genes, and six nuclear microsatellites (nSSRs) were studied and supplemented with ecological niche modeling (ENM) to infer its phylogeographic history. Populations with the same cpDNA private haplotypes and high haplotype diversity are mainly located in the CLP or scattered around northeast China and the coastal region. Spatial expansion was detected using a neutrality test and mismatch distribution, which may result in a widely distributed ancestral cpDNA haplotype, especially outside of the CLP. For nuclear DNA, private haplotypes are also distributed mainly in the CLP. ENM shows that the northern distribution of S. tuberculata has recently been occupied from the southern CLP and has experienced habitat loss in the south. In nSSRs, STRUCTURE clustering identified two genetic lineages, which are distributed in the west (green) and east (red), respectively, and many populations displayed pure green components, while pure red cluster populations were barely found. Genetic differentiation is significantly correlated with geographic distance, although genetic diversity is uniformly distributed. Thus, S. tuberculata populations probably survived the LGM in the southern CLP and experienced post-glacial expansion. The wind-dispersed pollen gene flow could bring a majority of the genetic composition to the front during spatial expansion, resulting in uniformly distributed genetic diversity. In combination with vegetation and climate changes since the LGM, we conclude that drought-enduring species, especially herb species, are likely preserved in the CLP during the LGM and experienced expansion to other regions in North China.